(untitled) (In situ, 2024)
The Crkvina site in the village of Šopot near Benkovac is located on the southern slope of Grubića glavica. The first investigations were carried out in the1920s, unearthing the remains of a church, church furnishings with the inscription of Duke Branimir and a cemetery dated to the early Middle Ages. Revision excavations and conservation of the church followed in the 1980s, and systematic research continued from 2016. In this campaign, the graves to the west of the church were investigated, actually two horizons of graves: the older, early medieval one, and the younger horizon dating to the 13th-14th centuries.